Tunable synthesis and characterization of phytoconjugated nanoparticles for water remediation - Julia Garvasis (Department of Chemistry, University of Calicut, 2022)
The ecosystem is under a severe threat due to the alarming increase in heavy metal ions caused by human activities and inadequate resource management. Chromium exists in both trivalent (Cr(III)) and hexavalent (Cr(VI)) forms, with Cr(VI) being highly hazardous and associated with teratogenic, mutagenic, and carcinogenic effects. Industries like electroplating and metal production contribute to Cr(VI) contamination in water bodies. Lead (Pb(II)), another toxic metal, poses even greater risks. Lead exposure affects the reproductive, neurological, and cardiovascular systems in adults, while children are more susceptible to long-term effects like neurological abnormalities. The textile industry's use of dyes causes pollution and contamination of rivers. Urgent and efficient cleanup measures are needed to address the inappropriate levels of heavy metals and toxins in water. Nanostructures have been used to remove heavy metal ions from water, but complex synthesis techniques and expensive chemicals limit their viability. Iron oxide nanoparticles (IONPs) offer a solution due to their magnetic properties, facilitating fast separation and recycling. Moreover, IONPs are nontoxic, biodegradable, biocompatible, and easily eliminated from the human body through iron metabolism pathways. Traditional coagulants like alum used in water treatment face challenges such as high dosage, sludge production, and inconsistent performance. Natural coagulants derived from plants are promising alternatives but face obstacles in quality control and cost-effectiveness. Exploring eco-friendly alternatives with commercial potential becomes imperative. The emerging field of biogenic synthesis leverages plant extracts to produce surface-modified NPs. Active secondary metabolites in the plant extracts act as potent reducing and capping agents, leading to the inclusion of organic functional groups on the, nanoparticles' surface. Invasive weeds pose a threat to biodiversity and crop yield. The thesis explores the utilization of invasive weed extracts as phytoreagents for metal oxide nanoparticle synthesis. By strategically manipulating the synthesis process, different phases of iron oxide, alumina, and aluminum sulfate nanoparticles can be generated, showcasing significant water remediation capabilities. The thesis is structured as follows: Chapter 1 provides a brief background, discusses green synthesis and alternative options, and presents an overview of the entire work. Chapter 2 focuses on the significance of selected plants, materials, instrumental techniques, and analytical procedures used. Chapter 3 details the synthesis of superparamagnetic phytogenic magnetite nanoparticles, their characterization, and their efficiency in removing Cr(VI) and Pb(II) from water. Chapter 4 explores the possibility of synthesizing magnetite nanoparticles using another invasive weed extract. Chapter 5 presents the tunable synthesis of iron oxide nanoparticles using the phytoreagents from Chapters 3 and 4, discusses their potential applications, and examines their cytotoxicity. Chapter 6 presents the synthesis and characterization of Aluminum sulfate NPs (AS- 6) and γ-alumina NPs (AS-10) using leaf extract of Hemigraphis alternata. AS-6 exhibited excellent coagulation performance for congo red dye and fluoride removal under various conditions, with high efficiency, low sludge production, reusability for up to five cycles, and potential cost- effectiveness, highlighting the promising prospects and unexplored aspects of phytogenic synthesis of coagulantsThe thesis aims to provide sustainable and effective solutions for heavy metal remediation, contributing to the preservation of ecosystems and human health.
1. Introduction -- 2. Materials and methods -- 3. Synthesis, characterization, and Cr(VI) and Pb(II) adsorption of PMNPs engineered using Chromolaena odorata flower extract -- 4. Synthesis, characterization and heavy metal removal of PMNPs engineered using Sphageneticola trilobata leaf extract -- 5. Phytogenic synthesis, characterization and application of iron oxide nanopigments -- 6. Phytogenic synthesis of nano aluminium sulphate coagulant for removal of congo red and fluoride from water
Thesis (Ph.D)- University of Calicut, Department of Chemistry, 2022
Keywords: Water purification; Water treatment; Phytoconjugated nanoparticles